PENGARUH STRES KERJA TERHADAP TURNOVER INTENTION DENGAN BURNOUT SEBAGAI VARIABEL MEDIASI - Resakomala, Putu Nilung Pradnya; Kartika Dewi, Anak Agung Sagung; Suwandana, I Gusti Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
The high and low levels of work stress and burnout experienced by employees can encourage the desire to leave the company. This study aims to analyze the effect of work stress on turnover intention with burnout as a mediating variable for marketing division employees. This research was conducted on employees of the marketing division of Karya Pak Oles Tokcer Bali company with a total sample taken of 60 employees and using the sampling method, namely saturated samples. The results of this study indicate that all hypotheses are accepted. Work stress has a positive and significant effect on turnover intention. Work stress has a positive and significant effect on burnout. Burnout has a positive and significant effect on turnover intention. Burnout significantly mediates the effect of work stress on turnover intention. The implications of the results of this study have been able to explain the attribution theory model used as the basis for preparing hypotheses and to be able to explain that the factors that influence turnover intention behavior are work stress and burnout experienced by employees.